A framework to create more mentally healthy workplaces: A viewpoint. (January 2018) - Petrie, Katherine; Joyce, Sadhbh; Tan, Leona; Henderson, Max; Johnson, Anya; Nguyen, Helena; Modini, Matthew; Groth, Markus; Glozier, Nicholas; Harvey, Samuel B
Mental illness is now the leading cause of long-term sickness absence among Australian workers, with significant costs to the individual, their employers and society more broadly. However, to date, there has been little evidence-informed guidance as to what workplaces should be doing to enhance their employees' mental health and wellbeing. In this article, we present a framework outlining the key strategies employers can implement to create more mentally healthy workplaces. The five key strategies outlined are as follows: (1) designing work to minimise harm, (2) building organisational resilience through good management, (3) enhancing personal resilience, (4) promoting early help-seeking and (5) supporting recovery and return to work. A narrative review is utilised to outline the theoretical evidence for this framework and to describe the available research evidence for a number of key example interventions for each of the five strategies. While each workplace needs to develop tailored solutions, the five strategy framework proposed in this review will hopefully provide a simple framework for employers and those advising them to use when judging the adequacy of existing services and considering opportunities for further enhancements.